Knowledge enhancement about pregnancy complications: Optimizing the role of high risk pregnancy prepared cadres - Ika Parmawati; Ayyu Sandhi; Wenny Artanty Nisman; Wiwin Lismidiati; Anik Rustiyaningsih; Itsna Luthfi Kholisa (Journal of Community Empowerment for Health, 2020)
Maternal death rate is one of the important health development indicators. Indonesian maternal mortality is still high due to both direct and indirect causes that occur during pregnancy and childbirth. High-risk pregnancy can present complications for both the mother and fetus, and demands early detection. Early detection requires involvement of the community, health cadre, medical officers, and government. There is a need to increase the community health cadre competency in the detection of pregnancy complications, especially high-risk pregnancy knowledge. This study used a quasi-experimental design without control group to determine the effect of training regarding pregnancy complications on community health worker’s knowledge in Wijimulyo, Nanggulan, Kulon Progo, Yogyakarta in October 2018. The research subjects were community health cadre workers chosen by purposive random sampling. There were 43 research subjects who were given pretests, training about complications of pregnancy, and posttests. The instrument used was a knowledge questionnaire about complications during pregnancy that consisted of 23 items with reliability of 0.865. There was significant difference between community health cadre’s knowledge about complications of pregnancy at pretest and posttest. These results indicate that training about pregnancy complications increases the knowledge of community health cadre workers concerning complications of pregnancy. Further research is needed to assess community health cadre’s skills in making early detection of pregnancy complications.